Stats aren`t everything: Learning strengths and weaknesses of cricket players - Behera, S.R.; Saradhi, V.V. (Machine Learning and Data Mining for Sports Analytics, 2020)
Strengths and weaknesses of individual players are understood informally by players themselves, coaches, and team management. However, there is no specific computational method to obtain strengths and weaknesses. The objective of this work is to obtain rules describing the strengths and weaknesses of cricket players. Instead of looking at the traditional statistics, which are nothing but the raw counts of certain events in the game, we focus on cricket text commentaries, which are written narratives giving a detailed description of a minute-by-minute account of the game while it is unfolding.